Sensory perception and reception of the Iraqi theatrical view" Presenting the play Umm Al-Khosh as a model" (Al-Academy, 2024)
This research deals with (sensory perception and reception of the Iraqi theatrical performance), considering perception is the process through which sensory information is recognized and interpreted, whether the stimuli are visual, auditory, or Tactile, olfactory, or gustatory, and given the importance of the topic, the researcher observed many philosophical opinions and theories. The religious and psychological aspects related to (sensory perception) were discussed to show the extent of the benefit of sensory perception of the Iraqi theatrical performance. The first chapter (the methodological framework) included the research problem, the limits of the research, and the most important terms used in the research. As for the second chapter (the theoretical framework), it included two sections, the first (the concept of sensory perception and its philosophy), and the second section on (the mechanism of perception), and the indicators for the theoretical framework. In the third chapter (research procedures), it was The researcher presented the play (Umm Al-Khosh) By its author and director (Mahmoud Abu Al-Abbas). The researcher chose the sample intentionally, adopting the descriptive analytical method. In the fourth chapter, the researcher also (discussed the results of the analysis) in accordance with the research objectives, as the researcher found that acting performance is supposed to be a means capable of awakening the imagination and feelings of the recipient, in order to feel Identify the characters and their situations so that he understands them in his mind, and the necessity of emphasizing the importance of vocal and performance technique. For the actor, with the aim of having a vocal and physical space that enables him to imitate an unlimited number of characters. Then the researcher confirmed the recommendations and proposals, and the researcher also arranged the sources and references in alphabetical order and without numbering.